Transmissão de preços no mercado internacional e brasileiro de açúcar - Graef, Cleber Eduardo (2017)
In this research, the price transmission between international and Brazilian sugar market was analyzed, from January 2003 to May 2016. The principles of market integration, price transmission and the framework of the Law of One Price, using time series econometric models (Augmented Dickey-Fuller test, Granger causality, Johansen cointegration test, and variance decomposition of prediction errors) were used as a theoretical approach. The results indicated a long-term relationship between international and domestic sugar prices; however, it was not observed for exchange rate. Thus, in the long-term, a variation of 1% in the sugar international price implies a variation of 0.42% in the domestic price, resulting an inelastic relation. The results did not validate the Law of One Price.